Digital literary map of Japan: a technical perspective = Nihon no dejitaru bungaku chizu - Born, Leo (Bunron, 2022)
The Digital Literary Map of Japan (DLM) is a project aimed at documenting and displaying geographical spots within Japan that convey literary associations or are found to have had significant impact on the literary-historic landscape of Japan over the centuries. In the context of the project, a web application with an online database has been developed in order to make the data easily accessible. This paper presents the technical infrastructure behind the web application and describes its core features as well as providing context for possible future directions of the application. The application is publicly hosted under https://literarymaps.nijl.ac.jp and can be accessed without a user account.